The adjuncts for endotracheal tube passage in simulated pediatric airways (AET‐SPA) study. Issue 3 (28th April 2022) - Gan, Khang Hee; Shepherd, Mike
Abstract: Objectives: To investigate whether the use of adjuncts such as stylet, railroaded bougie, and preloaded bougie increases first‐pass success rate and decreases time to successful intubation when intubating simulated infant airways using direct laryngoscopy. Methods: A crossover study using experienced practitioners (who were required to carry out emergency pediatric intubations as part of their usual practice) was completed. Participants completed a random sequence of 4 intubations in simulated "easy" airways and 4 intubations in simulated "difficult" airways, using naked endotracheal tube, stylet, railroaded bougie, and preloaded bougie on standardized infant airway manikins. First‐pass success rates and times to successful intubations were measured. Results: From June 1 to December 30, 2019, 109 participants performed a total of 872 intubation attempts. In the easy airway, both naked endotracheal tube (mean 96.3% [95% confidence interval 90.9%–99.0%]) and stylet (mean 98.2% [95% confidence interval 93.5%–99.8%]) had higher first‐pass success rates than railroaded bougie and preloaded bougie. In the difficult airway, stylet (mean 76.1% [95% confidence interval 67.0%–83.8%]) had the highest first‐pass success rate, followed by the naked endotracheal tube, and then both the railroaded bougie and preloaded bougie. Differences in first‐pass success rates were independent of the participants' numbers of previous pediatric intubations. Conclusion: Results of this simulation‐based study suggest that stylet should be used as the first attempt technique for infant intubations regardless of the presence or absence of predicted airway difficulty. This finding needs further validation using alternative models and in non‐simulation settings.